Optimal Rebalancing Strategy Using Dynamic Programming for Institutional Portfolios - Sun, Walter; C. Fan, Ayres; Chen, Li-Wei; Schouwenaars, Tom; A. Albota, Marius (Journal of Portfolio Management, 2006)
Institutional fund managers generally rebalance using ad hoc methods such as calendar basis or tolerance band triggers. We propose a different framework that quantifies the cost of a rebalancing strategy in terms of risk-adjusted returns net of transaction costs. We then develop an optimal rebalancing strategy that actively seeks to minimize that cost. We use certainty equivalents and the transaction costs associated with a policy to define a cost-to-go function, and we minimize this expected cost-to-go using dynamic programming. We apply Monte Carlo simulations to demonstrate that our method outperforms traditional rebalancing strategies like monthly, quarterly, annual, and 5% tolerance rebalancing. We also show the robustness of our method to model error by performing sensitivity analyses.